Molecular Simulation of the Separation of Some Amino Acid Enantiomers by β-Cyclodextrin in Gas-Phase - Alvira, Elena (Frontiers in Chemistry, 2020)
The complexes formed by beta-cyclodextrin and some amino acids (alanine, valine, leucine and isoleucine) in vacuo are studied by molecular mechanics and dynamics simulations. These methods have been improved with respect to our previous studies with amino acids, regarding the determination of molecular structures or initial enantiomer dispositions in the molecular dynamics trajectories. The greatest contribution to the interaction energy is from the van der Waals term, although the discrimination between enantiomers is due mainly to the electrostatic contribution. The lowest energy structures of the complexes obtained from molecular mechanics are inclusion complexes in which the carboxylic end of amino acids is pointing towards the narrow (D-) or wide rim (L-) of beta-cyclodextrin. The position probability density provided by molecular dynamics also confirms inclusion complex formation, because the guests spend most time inside the cavity of beta-cyclodextrin along its axis, with the carboxylic end pointing towards the narrow rim. The L-amino acids are the first eluted enantiomers in all cases and chiral discrimination increases with the size of guests, except leucine, which has the lowest capacity to discriminate. During the simulation, Ala and Val remain in weakly enantioselective regions, while Leu and Ile stay in zones with great chiral selectivity.